(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In construction sites, many laborers will be working for the completion of the construction project. To monitor these labours, many supervisors were appointed. Since labours are scattered in the ﬁeld, it will be diﬃcult to monitor them by the supervisors as well as round the clock, they will not be able to monitor whether the labours were wearing safety helmets or not. If it is a high-rise building construction, it will be difficult to locate the labourers at a given time and to communicate any information to them. To protect the workers and prevent accidents in construction sites, a novel design of autonomous system is proposed which monitors, localizes, and warns site laborers which results in saving project time and cost. The designed system is addressing the above said functionalities. The present invention is a low cost integrated system that alerts the supervisor with two signals, one for the helmet usage and another for the idle time of the labour. The labours may not be able to use the existing communication device during the working hours. The present invention alerts the emergency call information from the supervisor. The supervisors receive the location information of the particular labour through this intelligent system if necessary.